The Effectiveness of Regional Capital Participation in Regionally-Owned Enterprises: Principal-Agent Analysis of District Dividend Contributions - Rusito, Rusito; Jumanah, Jumanah (International Publisher (YAPENBI), 2026)
This study aims to analyze the effectiveness of regional capital participation in Regionally Owned Enterprises (BUMD) in increasing dividend contributions to Local Own-Source Revenue (PAD) of Lebak Regency in 2025 through the perspectives of Principal–Agent Theory and Public Value Governance. The study is motivated by the continued high fiscal dependence of local governments on central government transfers, while the contribution of BUMD dividends to local revenue remains relatively low. This research employs a descriptive qualitative approach supported by quantitative data, with data collected through documentary study and document analysis of regional financial reports, capital participation data, BUMD dividend reports, and related policy documents. The low level of effectiveness is influenced by agency problems, weak governance, limited operational capacity, insufficient institutional legitimacy and support, and the still limited public value generated by BUMD. Therefore, strengthening Good Corporate Governance (GCG), performance-based monitoring, business restructuring, and more measurable dividend targets is necessary so that regional capital participation can contribute more effectively to local revenue and public value creation.